(untitled) (Italian Journal of Public Health, 2012)
Public Health Genomics (PHG) has been defined as the responsible and effective translation of genome-based knowledge for the benefit of population health (Bellagio workshop, April 2005). The Italian Network of Public Health Genomics (GENISAP, http://istituti.unicatt.it/igiene_1830.html) was founded in 2006 as a follow-up of the PHG European Network (PHGEN) research activities. It is coordinated by Walter Ricciardi and Stefania Boccia from the Institute of Hygiene of the Faculty of Medicine of the Università Cattolica del Sacro Cuore, Rome. The aim of GENISAP is to integrate genomics into public health policy and practice in Italy in a responsible and effective manner. As such, GENISAP members elaborated the present document to describe the state of the art of PHG in Italy, in order to encourage the generation of evidence-based knowledge on genetic testing especially for common complex disorders. In Italy, about 560,000 genetic tests, including 311,069 cytogenetic and 248,691 molecular analyses, were recorded in 2007, but there is limited experience of translation of genomic testing for complex diseases into clinical practice (mostly on hereditary breast/ovarian and colorectal cancer syndromes). The collaboration between the Italian Health Ministry - that has introduced an action plan on genomics and predictive medicine in the 2010-2012 National Prevention Plan - and the GENISAP network will result in a fast advancement of Public Health Genomics in Italy.